An Analytical Model on the Execution of Transactional Memory - Yu, Xiao; He, Zhengyu; Hong, Bo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2010)
In this paper, we develop an analytical model of the execution of transactional memory (TM) systems. This model employs queuing theory to analyze the impact of an essential set of TM design parameters including the conflict rate, number of checkpoints, and implementation overhead, etc. The model is validated via extensive experiments. To demonstrate the effectiveness of the model, we further study the performance impact of two factors. Our study shows that, for a given TM-based program, the frequency of performing checkpoint can be carefully chosen to minimize the mean transaction completion time. Our study also demonstrated the importance of reducing implementation overhead.